Analysis of Tin Grade and Recovery in Monazite Retreatment with Three Disc Magnetic Separator - Adi Putri, Lintang Larasati; Probowati, Dyah; Amalia, Yasmina (Journal of Metallurgical Engineering and Processing Technology, 2024)
Retreatment is conducted to obtain tin that remains in the monazite tailings (2-3% Sn)  from the processing that has been carried out by PT. Timah. The purpose of this study is to analyse the presence of tin in monazite as well as the effect of magnetic intensity and opening feed on recovery and tin grade by employing a quantitative method of experimentation with three disc magnetic separator. In this study, magnetic intensity was used with disc 1, 2, and 3 respectively is 1.1 T, 1.3 T, 1.5 T (A); 1.3 T, 1.5 T, 1.7 T (B); and 1.5 T, 1.7 T, 1.9 T (C) with opening feed 0.4 cm and 0.8 cm. Based on the experiment, the highest tin grade is 7.33% with the largest combination of magnetic intensity, variation C, and opening feed 0.4 cm. Meanwhile, the highest recovery of 73.64% was obtained at the lowest magnetic intensity, variation A, with the same opening feed. It can be seen that by increasing the magnetic intensity, the tin content will be higher. Meanwhile based on some related experiment, the larger the opening feed, the higher the recovery. However, it should be noted that the opening feed used must not exceed 0.8 cm. If the opening feed used is equal or wider than 0.8 cm, it requires a strong magnetic intensity or the grade and recovery produced will not change significantly.